POTENSI PENGGUNAAN ABU BOILER INDUSTRI PULP DAN KERTAS SEBAGAI BAHAN PENGKONDISI TANAH GAMBUT PADA AREAL HUTAN TANAMAN INDUSTRI - Purwati, Sri; Soetopo, Rina; Setiawan, Yusup (Center for Pulp and Paper, 2007)
The utilization of boiler ash from bark burning in pulp and paper industry as a conditioning agent of peat gambut soil inindustrial plantation forest has been carried out. The utilization of boiler ash as much as 5 â€“ 10 kg/plant on peat soil,Â as a vegetation media of Acacia crasicarpa conducted in the green house and the field of timber estate. Its influences on productivity and environmental aspect has been observed for 12 months vegetation age. The results showed that there were a significant effect of boiler ash utilization on growth rate and productivity of plantations. Utilization up to 10 kg/plant or 10 tons/ha/plantation period was improving the physical, chemical, and biological properties of boiler soil without detrimental effects to the environment.